The photo-physiological costs associated with acute sediment stress events in three near-shore turbid water corals - Browne, Nicola; Precht, E.; Last, K.; Todd, P. (Inter-Research, 2014)
Many coral reef communities thriving in inshore coastal waters characterised by chronically high natural turbidity (>5 mg l-1) have adapted to low light (<200 µmol photons m-2 s-1) and high sedimentation rates (>10 mg cm-2 d-1). Yet, short (hours) acute sediment stress events driven by wind waves, dredging operations involving suction or screening, or shipping activities with vessel wake or propeller disturbance, can result in a rise in turbidity above the natural background level. Although these may not be lethal to corals given the time frame, there could be a considerable impact on photo-trophic energy production. A novel sediment delivery system was used to quantify the effects of 3 acute sediment resuspension stress events (turbidity = 100, 170, 240 mg l-1; sedimentation rates = 4, 9, 13 mg cm-2 h-1) on 3 inshore turbid water corals common in the Indo-Pacific (Merulina ampliata, Pachyseris speciosa and Platygyra sinensis). Coral photo-physiology response (respiration, net photosynthesis, and maximum quantum yield) was measured immediately after 2 h of exposure. The respiration rate increased (from 0.72-1.44 to 0.78-1.76 µmol O2 cm-2 h-1) as the severity of the acute sediment resuspension event increased, whereas the photosynthetic rate declined (from 0.25-0.41 to -0.19-0.25 µmol O2 cm-2 h-1). Merulina was the least tolerant to acute sediment resuspension, with a photosynthesis and respiration ratio (P/R ratio) of <1.0 when turbidity levels reached >170 mg l-1, while Platygyra was most tolerant (P/R > 1.0). Fluorescence yield data suggest that the rapid photo-acclimation ability of Platygyra enabled it to maintain a positive carbon budget during the experiments, illustrating species-specific responses to acute sediment stress events.